Hubungan Antara Motivasi Belajar dengan Hasil Belajar Pada Mata Pelajaran Akidah Akhlak di Kelas VIII MTs Ushuluddin Singkawang - Rizal Nurul Azmi; Dede Hidayat (Yayasan Syamil Quran Nunukan, 2025)
This research aims to determine student learning motivation, student learning outcomes and the relationship between learning motivation and student learning outcomes in the Aqidah Akhlak subject in class VIII MTs Ushuluddin Singkawang. This type of research is quantitative research using the interactive correlation method. The population in this study was class VIII students with a total of 258 students. The sample members in this study were 65 (Simple Random Sampling). The research results show that student learning motivation is moderate, student learning outcomes are good and there is a significant relationship between learning motivation and student learning outcomes as evidenced by the value of rxy>rttable = 0.796 > 0.244 which is in the strong category, so H0 is rejected and Ha is accepted.